1993
DOI: 10.1021/ma00064a032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(aniline-co-o-anisidine). A processable conducting copolymer

Abstract: An attempt has been made toward the chemical synthesis of poly(aniline-co-o-anisidine). It has been found that this conducting polymer is soluble in common organic solvents such as acetone, dimethylformamide (DMF), tetrahydrofuran (THF), and N-methylpyrrolidinone (NMP) at room temperature. The characterization of poly(aniline-co-o-anisidine) has been carried out using FTIR, UV-visible, DSC, and electrical conductivity measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 6 publications
6
66
0
Order By: Relevance
“…To prepare the base form, another portion of the finely ground polymer was suspended in a 0.1M NH 4 OH solution, stirred for 6 h, and filtered. 11,19 The elemental analysis of the obtained polymer base gave C, 41 MSA-doped polymers were prepared by adding 10 -20% MSA to a finely ground emerldine base and stirring for 6 h at room temperature. The deep green resultant polymers were filtered, washed with methanol, and dried in a vacuum for 24 h.…”
Section: Experimental Chemicalsmentioning
confidence: 99%
“…To prepare the base form, another portion of the finely ground polymer was suspended in a 0.1M NH 4 OH solution, stirred for 6 h, and filtered. 11,19 The elemental analysis of the obtained polymer base gave C, 41 MSA-doped polymers were prepared by adding 10 -20% MSA to a finely ground emerldine base and stirring for 6 h at room temperature. The deep green resultant polymers were filtered, washed with methanol, and dried in a vacuum for 24 h.…”
Section: Experimental Chemicalsmentioning
confidence: 99%
“…Since most of the conducting polymers are not processable, much of the efforts made in this field have been directed towards circumventing this problem. To solve this problem, various approaches have been tried, including addition of side groups to the polymer backbone [9], grafting of polymers to a non-conducting polymer [10], direct polymerization of intractable polymers into the final desired shape, making a composite of blend of conducting polymers [11] [12] and copolymerization [13]. Better processability may be achieved either by the synthesis on PANI in nano-micro scale particle, which is easier to disperse in a polymer matrix or by using an appropriate emulsifier which enhances the optical and electrical properties of PANI.…”
Section: Introductionmentioning
confidence: 99%
“…For most miscible polymer blends, the T gthe T g s of PANIS-HCl and PANIS-base from their DSC curves. Pandey et al 13 reported a T g value of 240ЊC for PANIS-base. However, their assignment of the glass transition appears doubtful as it is exothermic rather than endothermic and is complicated by the subsequent exothermic event.…”
Section: Resultsmentioning
confidence: 99%